Mariana serpentinite mud volcanism exhumes subducted seamount materials: implications for the origin of life. (6th January 2020) - Fryer, Patricia; Wheat, C. Geoffrey; Williams, Trevor; Kelley, Christopher; Johnson, Kevin; Ryan, Jeffrey; Kurz, Walter; Shervais, John; Albers, Elmar; Bekins, Barbara; Debret, Baptiste; Deng, Jianghong; et al.
Abstract : The subduction of seamounts and ridge features at convergent plate boundaries plays an important role in the deformation of the overriding plate and influences geochemical cycling and associated biological processes. Active serpentinization of forearc mantle and serpentinite mud volcanism on the Mariana forearc (between the trench and active volcanic arc) provides windows on subduction processes.  Here,  we present (1) the first observation of an extensive exposure of an undeformed Cretaceous seamount currently being subducted at the Mariana Trench inner slope; (2) vertical deformation of the forearc region related to subduction of Pacific Plate seamounts and thickened crust; (3) recovered Ocean Drilling Program and International Ocean Discovery Program cores of serpentinite mudflows that confirm exhumation of various Pacific Plate lithologies, including subducted reef limestone; (4) petrologic, geochemical and paleontological data from the cores that show that Pacific Plate seamount exhumation covers greater spatial and temporal extents; (5) the inference that microbial communities associated with serpentinite mud volcanism may also be exhumed from the subducted plate seafloor and/or seamounts; and (6) the implications for effects of these processes with regard to evolution of life. This article is part of a discussion meeting issue 'Serpentine in the Earth system'.